2018
DOI: 10.1155/2018/2839356
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Cytotoxic Activity of Three Streptomyces Strains Isolated from Guaviare River Sediments (Colombia, South America)

Abstract: Three Streptomyces strains isolated from Guaviare sediments (Colombia, South America) with cytotoxic activity against prostate cancer (PC3), breast cancer (MDA-MB-231), and lung cancer (A549) line cells were studied. The present investigation reveals the enhancement of the cytotoxic activity evaluating different values of pH, carbon sources (sucrose, glucose, xylose, maltose, and starch), and nitrogen sources (malt extract, yeast extract, meat extract, peptone, and potassium nitrate). Based on the response sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Micromonospora maritima D10-9-5 100.00 Some species in this study have been reported successful isolated from various samples such as soil, plant, pollutant water, coastal, sea sediment, or human body (Carro et al, 2018;Luo, Hu, Peng, Zhang, & Wang, 2015;Wibberg et al, 2018;Klymyshin et al, 2013;Bourbour, Keikha, & Faghri, 2018;Tsang et al, 2016;Chen, Tang, Mori, & Wu, 2012;Kumar et al, 2016;Xie et al, 2016a). The isolates have been reported as a source of several secondary metabolites were Micromonospora halophytica (Carro et al, 2018), Microbacterium ginsengisoli (Palaniappan et al, 2010), Streptomyces avellaneus (Ramirez-Rodriguez et al, 2018), Streptomyces bungoensis (Michael et al, 2017), Streptomyces chartreusis (Wibberg et al, 2018), Streptomyces echinatus (Klymyshin et al, 2013), Streptomyces griseoluteus (Luo et al, 2015), Streptomyces griseoruber (Wang, Peng, Zhang, Hui, & Hu, 2014), Streptomyces neopeptinius (Goudjal et al, 2016), Streptomyces polychromogenes (Mitsukura, Sakamoto, Kubo, Yoshida, & Nagasawa, 2010) , Streptomyces termitum (Sales et al, 2017), and Streptomyces violaceorectus (Fallah, 2018).…”
Section: Identification Of Actinomycetes Based On 16 S Rrna Gene Sequ...mentioning
confidence: 63%
“…Micromonospora maritima D10-9-5 100.00 Some species in this study have been reported successful isolated from various samples such as soil, plant, pollutant water, coastal, sea sediment, or human body (Carro et al, 2018;Luo, Hu, Peng, Zhang, & Wang, 2015;Wibberg et al, 2018;Klymyshin et al, 2013;Bourbour, Keikha, & Faghri, 2018;Tsang et al, 2016;Chen, Tang, Mori, & Wu, 2012;Kumar et al, 2016;Xie et al, 2016a). The isolates have been reported as a source of several secondary metabolites were Micromonospora halophytica (Carro et al, 2018), Microbacterium ginsengisoli (Palaniappan et al, 2010), Streptomyces avellaneus (Ramirez-Rodriguez et al, 2018), Streptomyces bungoensis (Michael et al, 2017), Streptomyces chartreusis (Wibberg et al, 2018), Streptomyces echinatus (Klymyshin et al, 2013), Streptomyces griseoluteus (Luo et al, 2015), Streptomyces griseoruber (Wang, Peng, Zhang, Hui, & Hu, 2014), Streptomyces neopeptinius (Goudjal et al, 2016), Streptomyces polychromogenes (Mitsukura, Sakamoto, Kubo, Yoshida, & Nagasawa, 2010) , Streptomyces termitum (Sales et al, 2017), and Streptomyces violaceorectus (Fallah, 2018).…”
Section: Identification Of Actinomycetes Based On 16 S Rrna Gene Sequ...mentioning
confidence: 63%
“…Our results indicate that the crude extract from Streptomyces gramineus TBRC 15927 was not toxic to the L-929 mouse fibroblast cells, with an IC 50 value of 0.029 ± 0.008 µg/mL (0.029 ppm). According to the report by Ramirez-Rodriguez et al [ 56 ], the toxicity of the L-929 mouse fibroblast cells was tested with Doxorubicin (1–25 ppm) as a standard substance. They concluded that crude extracts with an IC 50 value of less than 50 ppm are not significantly toxic to mammal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous species of the genus Streptomyces are known to produce many bioactive compounds and pigments that have demonstrated anti-tumour activity. In the search for a novel anticancer medication, S. aburaviensis and S. psammoticus are preferred possibilities [ 64 ]. S. gresioaurianticus JUACT 01 produces a yellow-coloured pigment that induces apoptosis in HeLa and HepG2 cell lines and is nontoxic to the human lymphocytes and is also a promising candidate for further investigations [ 65 ].…”
Section: Application Of the Bacterial Pigments In The Pharmaceutical ...mentioning
confidence: 99%